Technology diffusion, abatement cost, and transboundary pollution - Nori Tarui; Geoffrey Heal (Fondazione Eni Enrico Mattei (FEEM), 2008)
This paper studies countries' incentives to develop advanced pollution abatement technology when technology may spillover across countries and pollution abatement is a global public good. We are motivated in part by the problem of global warming: a solution to this involves providing a global public good, and will surely require the development and implementation of new technologies. We show that at the Nash equilibrium of a simultaneous-move game with R&D investment and emission abatement, whether the free rider effect prevails and under-investment and excess emissions occur depends on the degree of technology spillovers and the effect of R&D on the marginal abatement costs. There are cases in which, contrary to conventional wisdom, Nash equilibrium investments in emissions reductions exceed the first-best case.
Keywords: Q50; H87; D70; 330; International Environmental Agreement; Pollution Abatement Costs; Endogenous Technological Change